Isolation and Cytotoxic Activities of Two New 2-Pyridone Alkaloids with Unique Structures from the Beibu Gulf Coral-Derived Acremonium sclerotigenum GXIMD 02501 - Yuning Qin; Xinjian Qu; Miaoping Lin; Hong Zhang; Huangxue Qin; Chenghai Gao; Yonghong Liu; Xuefeng Zhou; Xiaowei Luo (Journal of Ocean University of China, 2026)

Neurotoxic risks of long-term environmental exposure to pesticides: a review - Yumeng Leng; Ye Zeng; Yuning Zhang; Jialin Zhang; Hao Xin; Mingyang Hou; Siman Ma; Hong Zhang (Chemico-Biological Interactions, 2025)

Protein Disulfide Isomerase Endoplasmic Reticulum Protein 57 (ERp57) is Protective Against ALS-Associated Mutant TDP-43 in Neuronal Cells - Sonam Parakh; Emma R. Perri; Marta Vidal; Zeinab Takalloo; Cyril J. Jagaraj; Prachi Mehta; Shu Yang; Colleen J. Thomas; Ian P. Blair; Yuning Hong; Julie D. Atkin (NeuroMolecular Medicine, 2024)
Amyotrophic Lateral Sclerosis (ALS) is a severe neurodegenerative disease affecting motor neurons. Pathological forms of Tar-DNA binding protein-43 (TDP-43), involving its mislocalisation to the cytoplasm and the formation of misfolded inclusions, are present in almost all ALS cases (97%), and ~ 50% cases of the related condition, frontotemporal dementia (FTD), highlighting its importance in neurodegeneration. Previous studies have shown that endoplasmic reticulum protein 57 (ERp57), a member of the protein disulphide isomerase (PDI) family of redox chaperones, is protective against ALS-linked mutant superoxide dismutase (SOD1) in neuronal cells and transgenic SOD1 G93A mouse models. However, it remains unclear whether ERp57 is protective against pathological TDP-43 in ALS. Here, we demonstrate that ERp57 is protective against key features of TDP-43 pathology in neuronal cells. ERp57 inhibited the mislocalisation of TDP-43 M337V from the nucleus to the cytoplasm. In addition, ERp57 inhibited the number of inclusions formed by ALS-associated variant TDP-43 M337V and reduced the size of these inclusions. ERp57 was also protective against ER stress and induction of apoptosis. Furthermore, ERp57 modulated the steady-state expression levels of TDP-43. This study therefore demonstrates a novel mechanism of action of ERp57 in ALS. It also implies that ERp57 may have potential as a novel therapeutic target to prevent the TDP-43 pathology associated with neurodegeneration.

Target-site and non-target-site based resistance to clodinafop-propargyl in wild oats (Avena fatua L.) - Yujun Han; Ying Sun; Hong Ma; Ruolin Wang; Yuning Lan; Haifeng Gao; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2023)

Residue screening and analysis of enrofloxacin and its metabolites in real aquatic products based on ultrahigh-performance liquid chromatography coupled with high resolution mass spectrometry - Jinxia Dai; Ye Wang; Hui Lin; Yanmin Sun; Yuning Pan; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Determination of chlorpromazine and its metabolites in animal-derived foods using QuEChERS-based extraction, EMR-Lipid cleanup, and UHPLC-Q-Orbitrap MS analysis - Jinxia Dai; Hui Lin; Yuning Pan; Yanmin Sun; Ye Wang; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Reduced glycodeoxycholic acid levels are associated with negative clinical outcomes of gestational diabetes mellitus - Bo Zhu; Zhixin Ma; Yuning Zhu; Lei Fang; Hong Zhang; Hongwei Kong; Dajing Xia (Journal of Zhejiang University-SCIENCE B, 2021)